Strategi Dinas Pariwisata dalam Menunjang Pendapatan Asli Daerah (PAD) - Siti Meliyani (JOPPAS: Journal of Public Policy and Administration Silampari, 2019)
The purpose of this study was to determine the factors that influence the success of the Tourism Office in Supporting Local Original Revenue (PAD) in Sukabumi Regency from PAD Bumi Perkumpang Cinumpang using the first dimension Dess and Miller: (1) Targets (2) Policies (3) ) Plans. This study used a qualitative method with 6 informants and data collection techniques of observation, interviews, documentation. Data analysis procedures using the model proposed by Bogdan. The results showed that the strategy of the Department of Tourism in Supporting Regional Original Revenue (PAD) has been going well, marked by the target of local original income in the Cinumpang Campsite has increased. Targets and policies, plans, that in each dimension have been said to be good in their strategies. While the inhibiting factor is the lack of support from the public about the importance of maintaining and a tourist attraction. In conclusion, the strategy of the Department of Tourism in Supporting Local Revenue (PAD) has been going well. Keywords: Strategy, Regional Original Revenue.